Cognitive interventions to reduce diagnostic error: a narrative review. Issue 7 (27th April 2012) - Graber, Mark L; Kissam, Stephanie; Payne, Velma L; Meyer, Ashley N D; Sorensen, Asta; Lenfestey, Nancy; Tant, Elizabeth; Henriksen, Kerm; LaBresh, Kenneth; Singh, Hardeep
Abstract : Background: Errors in clinical reasoning occur in most cases in which the diagnosis is missed, delayed or wrong. The goal of this review was to identify interventions that might reduce the likelihood of these cognitive errors. Design: We searched PubMed and other medical and non-medical databases and identified additional literature through references from the initial data set and suggestions from subject matter experts. Articles were included if they either suggested a possible intervention or formally evaluated an intervention and excluded if they focused solely on improving diagnostic tests or provider satisfaction. Results: We identified 141 articles for full review, 42 reporting tested interventions to reduce the likelihood of cognitive errors, 100 containing suggestions, and one article with both suggested and tested interventions. Articles were classified into three categories: (1) Interventions to improve knowledge and experience, such as simulation-based training, improved feedback and education focused on a single disease; (2) Interventions to improve clinical reasoning and decision-making skills, such as reflective practice and active metacognitive review; and (3) Interventions that provide cognitive 'help' that included use of electronic records and integrated decision support, informaticians and facilitating access to information, second opinions and specialists. Conclusions: We identified a wide range of possible approaches to reduce cognitive errors in diagnosis. Not all the suggestions have been tested, and of those that have, the evaluations typically involved trainees in artificial settings, making it difficult to extrapolate the results to actual practice. Future progress in this area will require methodological refinements in outcome evaluation and rigorously evaluating interventions already suggested, many of which are well conceptualised and widely endorsed.